Ambivalensi Abdurahman Wahid dalam Wacana Keislaman Postkolonial dan Implikasinya bagi Dialog Antara Islam dan Barat - M. Ridho Syabibi; Hawasi (DAWUH : Islamic Communication Journal, 2024)
This article attempts to elaborate on the ambivalence of Abdurrahman Wahid or Gus Dur in his postcolonial Islamic discourse and its implications in the dialogue between Islam and the West. The idea of ​​Gus Dur's postcolonial Islamic discourse can be found in works in the form of articles and essays. In these works, Gus Dur appears as an open-minded and liberal intellectual scholar in accepting and responding to Western thought and ideology. These Western thoughts and ideologies are contextualized by Gus Dur into his Islamic discourse. When the majority of Muslim intellectuals and ulamas tend to be resistant to the West, Gus Dur actually eclectically accepts the development of Western thought and ideology. By using postcolonial reading and the Ricoeurian hermeneutic method, this article finds a hybrid identity between Islam and the West in the Islamic discourse developed by Gus Dur. The hybrid identity possessed by Gus Dur is used to build his postcolonial Islamic discourse that is compatible with democracy. The postcolonial Islamic discourse developed by Gus Dur was practiced in the struggle to strengthen Pancasila democracy and humanism in Indonesia. Gus Dur's postcolonial Islamic discourse respects the plurality of Indonesian society in terms of ethnicity, culture, and religion. Gus Dur's respect for plurality was built by his cosmopolitan thinking and made him open to identity hybridity. The hybrid process of Gus Dur's postcolonial Islamic discourse produced ambivalence in the form of mimicry and mockery of the West found in his writings on philosophy, democracy, literature, and language. Therefore, Gus Dur's hybrid ideas are relevant to bridging the global dialogue between Islam and the West which he also voiced in international forums.